IMF after the Asian crisis : merits and limitations of the long-term development partner role - Mosley, Paul (2001)
Reviews both sides of the debate whether the IMF should retain, improve or abandon a set of additional policy instruments and responsibilities it has taken on over the last twenty years. Concludes that the available evidence does not allow the case for the alternative role - that of long-term development partner - to be rejected.